1975
DOI: 10.4039/ent107225-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control Attempts by Introductions Against Pest Insects in the Field in Canada

Abstract: This is an analysis of the attempts to colonize at least 208 species of parasites and predators on about 75 species of pest insects in the field in Canada. There was colonization by about 10% of the species that were introduced in totals of under 5,000 individuals, 40% of those introduced in totals of between 5,000 and 31,200, and 78% of those introduced in totals of over 31,200. Indications exist that initial colonizations may be favoured by large releases and by selection of release sites that are semi-isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 6 publications
5
60
0
Order By: Relevance
“…The few previous studies that have included information on propagule size have found it to be the major correlate of success, but to date such studies have been either localized in extent (Newsome & Noble 1986;Veltman et al 1996;Duncan 1997) or limited in scope (Beirne 1975;Dawson 1984;Greustad 1999). Our results show that propagule pressure is the primary determinant of introduction success for an entire higher taxon, where releases have occurred for a variety of reasons (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The few previous studies that have included information on propagule size have found it to be the major correlate of success, but to date such studies have been either localized in extent (Newsome & Noble 1986;Veltman et al 1996;Duncan 1997) or limited in scope (Beirne 1975;Dawson 1984;Greustad 1999). Our results show that propagule pressure is the primary determinant of introduction success for an entire higher taxon, where releases have occurred for a variety of reasons (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Classical biological control literature is divided over whether it is a better strategy to release a large number of parasitoids in a few places (e.g., Beirne 1975;Cameron et al 1993;Grevstad 1999) or a small number of insects in many places (e.g., Campbell 1976;Memmot et al 1998) to increase the probability of establishment. In the present study, over 10,000 D. kraussii adults were released over eight separate occasions, which is a large number in reference to the threshold of 1,000 insects recommended by Hopper and Roush (1993) as necessary to ensure establishment of introduced parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control literature is divided over whether it is a better strategy to release a large number of individuals in a few places (e.g., Beirne 1975;Cameron et al 1993;Grevstad 1999), or a small number of individuals in many places (e.g., Campbell 1976;Memmott et al 1998) to increase the overall probability of establishment. The optimum establishment strategy is likely to vary with species and environment.…”
Section: Discussionmentioning
confidence: 99%